Leaf Pruning Increased Seed Yield and Leaf Production of Cowpea (Vigna unguiculata L. Walp) - Hartini Kilbaren, Muji; Purnamawati, Heni; Melati, Maya (Department of Agronomy and Horticulture, IPB University, 2023)
The leaves and pods of cowpea (Vigna unguiculata L. Walp) have potential uses as vegetables. This research aimed to assess the impact on cowpea growth and seed yield through different pruning times, methods, intensities, and their interactions. Conducted at the Cikabayan Experimental Field, IPB University, between April and August 2022, the study employed a randomized complete block design with three factors and three replications. The first factor, pruning time (5 and 7 weeks after planting, WAP), represented vegetative and generative phases. The second factor involved pruning methods (leaf and shoot), while the third focused on pruning intensity (0, 10, 30, and 50% of leaf numbers). This resulted in 16 treatment combinations, replicated three times, yielding 48 experimental plots. Measured variables included pruned leaf count, pruned leaf weight, total leaf count, plant fresh and dry weights, cowpea plant C/N ratio analysis, pod wet and dry weights, pod count, pod length, seeds per pod count, 100-seed weight, dry seed weight per plant, dry seed weight per plot, and cowpea seed productivity. Results highlighted significant effects of pruning time, method, and intensity on leaf count, shoot fresh and dry weights, and C/N ratio of cowpea plants after two weeks of pruning. However, the treatments did not significantly influence cowpea seed yield. Pruning cowpea leaves led to an average pruned leaf weight of 30 g per plant, offering a nutritious vegetable source without compromising cowpea seed yield. These leaves commanded a market price of approximately Rp. 6000 per kg, transforming them into a valuable economic asset when utilized as vegetables, thus contributing to the sale of nutritious food.